2021
DOI: 10.4081/ejh.2021.3174
|View full text |Cite
|
Sign up to set email alerts
|

Immunopositivity for Siglec-15 in gastric cancer and its association with clinical and pathological parameters

Abstract: The sialic acid-binding immunoglobulin-type lectin Siglec-15 is a promising target to cancer immunotherapy in several tumor types. The present study aimed to investigate Siglec-15 expression in gastric cancer (GC) patient tissue and to evaluate its clinical value. Siglec-15 expression was evaluated by immunohistochemistry with 71 patients. Siglec-15 staining was observed in tumor cells of 53 (74.64%) patients, with significant association with histologic classification and angiolymphatic invasion (p<0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In the present study, our findings also revealed that Siglec‐15 positivity was related to improved PFS and DSS, and was an independent predictor of prognosis in PDAC. In addition, a previous study demonstrated that Siglec‐15 expression was significantly more frequent in AJCC II stage and well‐differentiated gastric cancer [ 31 ], while positive expression of Siglec‐15 was associated with the presence of perineural invasion and well and moderate differentiation in our study. The pan‐cancer analysis and our data suggest that the expression of Siglec‐15 may have distinct prognostic implications in different types of cancer.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the present study, our findings also revealed that Siglec‐15 positivity was related to improved PFS and DSS, and was an independent predictor of prognosis in PDAC. In addition, a previous study demonstrated that Siglec‐15 expression was significantly more frequent in AJCC II stage and well‐differentiated gastric cancer [ 31 ], while positive expression of Siglec‐15 was associated with the presence of perineural invasion and well and moderate differentiation in our study. The pan‐cancer analysis and our data suggest that the expression of Siglec‐15 may have distinct prognostic implications in different types of cancer.…”
Section: Discussionsupporting
confidence: 73%
“…Li et al demonstrated that Siglec‐15 overexpression was associated with worse overall survival (OS) and relapse‐free survival (RFS) in kidney cancer, and they also found that Siglec‐15 was correlated with poor PFS, but not OS, in lung adenocarcinoma [ 30 ]. Quirino et al found that Siglec‐15 expression was not related to OS and RFS in gastric cancer [ 31 ], and Hao et al similarly demonstrated that Siglec‐15 was not associated with OS in early NSCLC [ 32 ]. In contrast, high Siglec‐15 expression was correlated with better OS in bladder cancer, invasive breast carcinoma, thyroid cancer, endometrioid carcinoma, and head and neck squamous cell carcinoma and with better RFS in ovarian cancer, liver cancer, and endometrioid carcinoma, which was consistent with our results in PDAC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Li et al, high Siglec-15 expression was associated with poor OS in GC (HR = 4.87, 95% CI = 1.42–15.4, p = 0.006) [ 163 ]. At the same time, in other studies, the expression of Siglec-15 in GC was not associated with OS [ 160 , 164 ].…”
Section: Immune Checkpoint Expression In Connection With Clinical Features and The Therapeutic Efficacy Of Their Inhibitionmentioning
confidence: 66%
“…Quirino et al reported the association of Siglec-15 expression with such clinicopathological characteristics as the TNM stage ( p = 0.01), histological grade ( p = 0.0022) and angiolymphatic invasion ( p = 0.041) [ 164 ].…”
Section: Immune Checkpoint Expression In Connection With Clinical Features and The Therapeutic Efficacy Of Their Inhibitionmentioning
confidence: 99%
“…Next to its expression on myeloid cells, Siglec-15 was observed on stromal cells and even on tumor cells (28). Siglec-15 expression on tumor cells was verified by others on several types of cancer, such as lymphoma, gastric cancer and acute myeloid leukemia (29)(30)(31). Similarly, Siglec-8 has been reported to be expressed by breast cancer cells (32).…”
Section: Siglec Expression Within the Tmementioning
confidence: 72%